Un astrónomo, tres continentes, siete instituciones y millares de estrellas. La experiencia global de Jürgen Stock en los inicios de la astronomía en Chile - Bárbara Silva (Nuevo mundo - Mundos Nuevos, 2022)
In 1959, German astronomer Jürgen Stock arrived in Chile to do site testing for an American project of astronomical observation. We can understand this expedition as the beginning of a long and accelerated path towards astronomical development in Chile, currently ongoing. At first sight, Stock’s biography seems to explain the process. However, in deeper analysis, even though Stock’s life certainly influenced this process, these first steps of contemporary astronomy in Chile need to be understood from the intersection of other individual initiatives, as well as from historical processes, with wider temporal and spatial scope. In this way, through the case of early transnational astronomy in Chile and the biographies that influenced it, it is possible to discuss and reflect on the role of individuals as subjects with historical agency. Likewise, this scientific experience offers an opportunity to analyze the tension and relationship between those biographies and a time-based and spatial framework enclosed within global categories.